Dyke Davidoff Masson syndrome: rare cause of hemiparesis - Rajan, A. R.; Chordia, Prisha; Gautam, A. A.; Bansode, Priyanka (International Journal of Contemporary Pediatrics, 2025)
Dyke-Davidoff-Masson syndrome (DDMS) is a rare clinical entity caused by a neurological disorder that results from cerebral injury in -utero or in early infancy resulting in unilateral brain atrophy. The resulting clinical presentation is with hemiplegia, seizures, developmental delay and behavioural disorders. Our case is a 12-year-old boy who presented with hemiparesis, poor scholastic performance and seizures. The MRI brain revealed a decreased volume of the right cerebral hemisphere with gliotic change in the frontal region. The right cerebral peduncle appeared small in size with cystic encephalomalacia and thinning of the corpus callosum. MRI findings were suggestive of DDM syndrome. The electroencephalogram was abnormal. An early recognition will help reduce disability with physiotherapy and anticonvulsant therapy.